Wide-Angle Ceramic Retroreflective Luneburg Lens Based on Quasi-Conformal Transformation Optics for Mm-Wave Indoor Localization - Kaděra, Petr; Sánchez-Pastor, Jesús; Eskandari, Hossein; Tyc, Tomáš; Sakaki, Masoud; Schüßler, Martin; Jakoby, Rolf; Benson, Niels; Jiménez-Sáez, Alejandro; Láčík, Jaroslav (IEEE, 2022)
This paper presents a quasi-conformal transformation optics (QCTO) based three-dimensional (3D) retroreflective attened Luneburg lens for wide-angle millimeter-wave radio-frequency indoor localization. The maximum detection angle and radar cross-section (RCS) are investigated, including an impedance matching layer (IML) between the lens antenna and the free-space environment. The 3D QCTO Luneburg lenses are fabricated in alumina by lithography-based ceramic manufacturing, a 3D printing process. The manufactured structures have a diameter of 29.9 mm (4 lambda_0), showing a maximum realized gain of 16.51 dBi and beam steering angle of +-70° at 40 GHz. The proposed QCTO Luneburg lens with a metallic reflective layer achieves a maximum RCS of -20.05 dBsqm at 40 GHz with a wide-angle response over +-37°, while the structure with an IML between the lens and air improves these values to a maximum RCS of -15.78 dBsqm and operating angular response between +-50°.

This paper presents a quasi-conformal transformation optics (QCTO) based three-dimensional (3D) retroreflective attened Luneburg lens for wide-angle millimeter-wave radio-frequency indoor localization. The maximum detection angle and radar cross-section (RCS) are investigated, including an impedance matching layer (IML) between the lens antenna and the free-space environment. The 3D QCTO Luneburg lenses are fabricated in alumina by lithography-based ceramic manufacturing, a 3D printing process. The manufactured structures have a diameter of 29.9 mm (4 lambda_0), showing a maximum realized gain of 16.51 dBi and beam steering angle of +-70° at 40 GHz. The proposed QCTO Luneburg lens with a metallic reflective layer achieves a maximum RCS of -20.05 dBsqm at 40 GHz with a wide-angle response over +-37°, while the structure with an IML between the lens and air improves these values to a maximum RCS of -15.78 dBsqm and operating angular response between +-50°.
Wide-Angle Ceramic Retroreflective Luneburg Lens Based on Quasi-Conformal Transformation Optics for Mm-Wave Indoor Localization
Keywords: Transformaton optics; Luneburg lens; impedance matching; lens antenna; retrorefleector; ceramic 3D printing; indoor localization; mm-wave; artificial dielectrics; chipless RFID; Transformaton optics; Luneburg lens; impedance matching; lens antenna; retrorefleector; ceramic 3D printing; indoor localization; mm-wave; artificial dielectrics; chipless RFID